Impact of Instructional Materials on the Teaching of Mathematics in Selected Secondary Schools in Mpigi District. - Bongole, Alex (Kabale University, 2024)
This study aimed to investigate the influence of instructional materials on student's academic performance in mathematics. The use of instructional materials in teaching has been a subject of interest and debate in the education community, with proponents arguing that they enhance learning experiences and outcomes. This research seeks to provide empirical evidence on the topic by examining the use of instructional materials on student's academic performance in mathematics. This study aimed to find out the impact of instructional materials on the teaching of mathematics in selected secondary schools in the Mpigi district. The methodology for the study was based on unstructured interviews with a qualitative design, and simple random and purposive sampling. Some selected secondary schools in the Mpigi district were the study area. Findings: The findings showed that the instructional materials are available and their use improved the academic performance of students in mathematics. Therefore, the findings had the potential to inform educational practices and policies, helping educators make informed decisions about the integration of instructional materials into their teaching methods. Teachers should put emphasis on the use of visual resources, and endeavor to use graphical illustrations in designing instructional material, and teachers should always use real objects as a pre-requisite for the academic performance of pupils in Mathematics.